A Phase 1, Randomized, Single-Ascending-Dose Study To Investigate the Safety, Tolerability, and Pharmacokinetics of DSTA4637S, an Anti-Staphylococcus aureus Thiomab Antibody-Antibiotic Conjugate, in Healthy Volunteers - Peck, Melicent (Antimicrob Agents Chemother, 2019)
Staphylococcus aureus causes serious bacterial infections with high morbidity and mortality, necessitating the discovery of new antibiotics. DSTA4637S is a novel antibody-antibiotic conjugate designed to target intracellular S. aureus that is not adequately eliminated by current standard-of-care antibiotics. DSTA4637S is composed of an anti-S. aureus Thiomab human immunoglobulin G1 (IgG1) monoclonal antibody linked to a novel rifamycin-class antibiotic (4-dimethylaminopiperidino-hydroxybenzoxazino rifamycin [dmDNA31]) via a protease-cleavable linker. Phagocytic cells ingest DSTA4637S-bound S. aureus, and intracellular cathepsins cleave the linker, releasing dmDNA31and killing intracellular S. aureus. This first-in-human, randomized, double-blind, placebo-controlled, single-ascending-dose phase 1 trial analyzed the safety, pharmacokinetics, and immunogenicity of DSTA4637S in healthy volunteers. Thirty healthy male and female volunteers, 18–65 years old, were randomized into five cohorts receiving single intravenous (i.v.) doses of 5, 15, 50, 100, and 150 mg/kg of DSTA4637S or placebo (4 active:2 placebo). Subjects were followed for 85 days after dosing. No subject withdrew from the study, and no serious or severe adverse events occurred. One moderate infusion-related reaction (150 mg/kg DSTA4637S) occurred. No clinically meaningful or dose-related changes in laboratory parameters or vital signs occurred. Pharmacokinetics of plasma DSTA4637S conjugate and serum DSTA4637S total antibody were dose proportional. Systemic exposure of unconjugated dmDNA31 was low. No DSTA4637S-induced anti-drug antibody responses were observed. DSTA4637S was generally safe and well tolerated as a single i.v. dose in healthy volunteers. DSTA4637S has a favorable safety and pharmacokinetic profile that supports future development as a novel therapeutic for S. aureus infections. (This study has been registered at ClinicalTrials.gov under identifier NCT02596399.)